Significance of Cattaneo-Christov heat flux in Darcy-Forchheimer transport of nanofluid with entropy optimization - Marei Saeed Alqarni; Umar Farooq; Umair Manzoor; Muhammad Imran; Taseer Muhammad; Hassan Waqas (Advances in Mechanical Engineering, 2022)
Darcy-Forchheimer transport of nanofluid comprising Ethylene glycol in Cattaneo-Christov heat flux across an extended cylinder with various slips is investigated in this paper. The influence of autocatalytic chemical reactions in the governing equations enrich the novelty of the proposed mathematical formula. The current challenge also includes an entropy minimization study of the governing equations. For the conversion of the nonlinear system to ODEs, a relevant transformations technique is used. For the calculation of a nonlinear set of linear equations, the bvp4c (shooting) method is coupled with the MATLAB program. Graphical drawings are used to examine the effects of the leading factors on occupied fields. The results demonstrate that a high magnetic parameter boosts the thermal profile while lowering the velocity. In addition, the velocity is reduced when the slip parameter is estimated. Furthermore, it was determined that as the thermal relaxation parameter was raised as the entropy number increases. The tabular data is included to support the current mathematical model.